Relevance of the extension of the educational offer of the technical baccalaurate in the "Isaac AcostaCalderón" Educational Unit - Rosero Almeida, Lilian Patricia; Rivadeneira Martínez, Alexis Ernesto (SATHIRI, 2019)
The present investigative work was oriented to determine the relevance of the expansion of the educational offer in the "Isaac Acosta" Educational Unit in the city of Tulcán, considering that in Carchi Province does not exist the Music Specialization, an option that, the Technical Baccalaureate of Arts in the institution already has. Its opening constitutes a different professional option that allows young people who have this talent to train with the necessary skills and enter in the labor market. Perform instrumental and vocal pieces and musical works; make arrangements, musical compositions basic and multimedia resource productions; and guide the work of artistic groups in the singing and execution of musical instruments, with efficiency, artistic skill and complying with Specific quality parameters. The present proposal reflected the feeling of a segment of the student population of the San Pedro District of Huaca " Tulcán. The present work finds its support in the quantitative - descriptive research known as a statistic research. The results clearly showed thatmost of the surveyed pronounced in favor of the diversification of the existent educative offer, being the first option, the creation of the Music Specialty, concluding that the extension of the Technical Baccalaureate in Arts, in the Specialty of Music in the Educational Unit "Isaac Acosta" is relevant, being this the answer to the need of training that has an important segment of the student population and that until now has not been attended, making possible to meet the requirements of the institutions public and private to have professionals in this field, allowing the province to continue being a national reference in the development of the Arts.
Keywords: Offer; Technical Baccalaureate; labor market